Broadband and Tunable High-Performance Microwave Absorption of an Ultralight and Highly Compressible Graphene Foam - Zhang, Yi; Huang, Yi; Zhang, Tengfei; Chang, Huicong; Xiao, Peishuang; Chen, Honghui; Huang, Zhiyu; Chen, Yongsheng (Advanced materials (Weinheim), 2015)
The broadband and tunable high‐performance microwave absorption properties of an ultralight and highly compressible graphene foam (GF) are investigated. Simply via physical compression, the microwave absorption performance can be tuned. The qualified bandwidth coverage of 93.8% (60.5 GHz/64.5 GHz) is achieved for the GF under 90% compressive strain (1.0 mm thickness). This mainly because of the 3D conductive network.